Time is out of joint: the transmedial hauntology of David Bowie. Issue 1 (2nd January 2019) - Perrott, Lisa
ABSTRACT: David Bowie's transformational engagement with stardom was complexly entwined with his long and creative relationship with hauntology. While referring us back in time, Bowie's songs and videos simultaneously haunt us about a lost future. Bowie engaged with hauntology initially by mimicking the sonic, visual and bodily gestures of many star performers. This developed into synthesised mimicry, which involved fusing the traits of several stars in order to create a coherent star persona. During the last decade of his life, Bowie perplexed his audience by calling up his own 'ghost stars', reconfiguring celebrity and expressing a persistent sense of 'future nostalgia'. In his last enigmatic gasp before exiting Earth, Bowie invited his audience to undertake a celebratory autopsy of his star status. His parting gifts were prescient hauntings of the future, poignantly stitched together with nods of tributary reference to artists he had borrowed from. Drawing on the concept of hauntology, this article examines a selection of musical and audiovisual outputs across five decades of Bowie's career, demonstrating how he stretched the possibilities of hauntology as a conceptual tool and an artistic strategy, and prepared the cultural bed for audience members and cultural participants to engage with hauntological media.